(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The purpose of this article is to describe a brief analysis of the criterion adopted by the Office of the Attorney General of the State of Tabasco, in the interpretation of article 140 of the National Code of Criminal Procedures (CNPP), regarding the crimes of robbery without violence, due to the fact that being placed at his disposal by a person with a criminal appearance of robbery without violence, arrested in flagrante delicto; the Prosecutor’s Office, which is an integral part of the actions of the State, specifically, those of investigating crimes of the common order, whose support is based on Article 21 of the Federal Constitution and 4 of the Organic Law of the State Attorney General’s Office ; As a result, it may violate human rights. In this sense, from the 2011 Constitutional reform regarding human rights, all authorities without exception must become protagonists of Human Rights defenders; The Office of the Prosecutor of the State of Tabasco, when placed on a person due to the circumstances described, is obliged to promote, respect, protect and guarantee their human rights, and consequently when interpreting the extremes of article 140 of the CNNP, to apply it to the aforementioned detained person, is obliged to carry out an exercise of weighting of rights.